Impact of Detour Tunnels in Metro Station Track Area on Ventilation and Thermal Environment of the Line Tunnel - TIAN Tingting; GAO Wei; WANG Fangmin; YU Tao (Chengshi guidao jiaotong yanjiu)
［Objective］ Due to the space limitation around some metro stations, the piston air shafts can not be installed outside the track area. To meet the ventilation requirements, the piston air shafts can be arranged within the station track area through a detour tunnel connecting with the main line tunnels outside the track area. At present, there are no relevant studies on the application of detour tunnel in improving the ventilation and thermal environment of tunnels. Therefore, it is necessary to analyze similar projects. ［Method］ In the case study of a metro line with a detour tunnel, a one-dimensional numerical simulation method is used to simulate and calculate the situation where piston air shafts are set in the station track area and a detour tunnel is constructed. The impact of setting the detour tunnel in station track area on the tunnel piston air volume of the entire line, the air volume of the piston air shafts, and the air temperature distribution in the tunnel is analyzed. ［Result & Conclusion］ When the detour tunnel is located at the outbound end of the station, the piston air volume in the section tunnel at the outbound end changes the most, with a maximum increase of 38.1 m3/s. Same is the air volume of the piston air shaft closest to the detour tunnel. The tunnel air temperature changes the most mainly in the station track area where the detour tunnel is located. The incoming air of the piston air shaft in the track area causes rapid drop of the air temperature at the outbound end in the station track area, with a maximum decrease of 1.8 ℃. The detour tunnel leads to more temperature drop in the track area where the train head stops, and the detour tunnel at the outbound end of the station has better control effect on the thermal environment than that at the inbound end of the station.